Gingival mask: A case report on enhancing smiles - Aashritha Shenava (Wolters Kluwer Medknow Publications, 2014)
Periodontal attachment loss in the maxillary anterior region can often lead to esthetic and functional clinical problems including disproportional and elongated clinical crowns and visible interdental embrasures. Gingival replacement prosthesis has historically been used to replace lost tissue. A gingival mask is an easily constructed and practical device to optimize the esthetic and functional outcome in these special situations while permitting cleansibility of the prosthesis and supporting tissues. This is a case report of a young female patient treated using silicon gingival veneer with a 2-year follow-up. The silicon gingival mask has enabled the patient to regain her lost smile and face people with newly found confidence also enhancing the esthetic appearance. Virtually, no problem was encountered during the 2 years of usage of the veneer and the patient continues to use it comfortably.